The Just War and Jihad - Amr G. E. Sabet (International Institute of Islamic Thought, 2007)
The fifteen chapters of this book bring together scholars from a variety of fields to examine and analyze what they perceive to be a relationship between religion and violence. Generating a feeling of déjà vu, they rehash previously developed assumptions, arguments, and biases that tend to ignore underlying causes related to the “existence of the sacred,” for reasons apparently beyond the domain of secular comprehension. The articles reiterate conventional secular arguments about the dangers of religious convictions on “peace” and tend to vary in quality and consistency, which reflects on the book’s overall merit. Although it is not feasible to go into each chapter’s details, it is important to underscore their basic thrust and common theme: the issue of legitimation and what confers legitimacy on action, be it violent in nature, such as in war or conflict, or simply legal and organizational. Hector Avalos (chapter 6) puts it candidly. In the “relative” framework of “empirico-rationalism,” he argues that religious violence is always “immoral,” positing that “life,” as a manifestation of that which “exists,” is worth more than that which does not exist (p. 113). However, this does not preclude war in the absolute. One arrives at this conclusion after reading J. Harold Ellens’ “The Obscenity of War” (chapter 2) as well as the Committee for the Scientific Examination of Religion’s (CSER) “Protocol on Religion, Warfare, and Violence” (chapter 15) ...